Mars Science Laboratory Curiosity Rover Megaripple Crossings up to Sol 710 in Gale Crater. Issue 3 (23rd February 2016) - Arvidson, Raymond E.; Iagnemma, Karl D.; Maimone, Mark; Fraeman, Abigail A.; Zhou, Feng; Heverly, Matthew C.; Bellutta, Paolo; Rubin, David; Stein, Nathan T.; Grotzinger, John P.; Vasavada, Ashwin R.
Abstract : After landing in Gale Crater on August 6, 2012, the Mars Science Laboratory Curiosity rover traveled across regolith‐covered, rock‐strewn plains that transitioned into terrains that have been variably eroded, with valleys partially filled with windblown sands, and intervening plateaus capped by well‐cemented sandstones that have been fractured and shaped by wind into outcrops with numerous sharp rock surfaces. Wheel punctures and tears caused by sharp rocks while traversing the plateaus led to directing the rover to traverse in valleys where sands would cushion wheel loads. This required driving across a megaripple (windblown, sand‐sized deposit covered by coarser grains) that straddles a narrow gap and several extensive megaripple deposits that accumulated in low portions of valleys. Traverses across megaripple deposits led to mobility difficulties, with sinkage values up to approximately 30% of the 0.50 m wheel diameter, resultant high compaction resistances, and rover‐based slip up to 77%. Analysis of imaging and engineering data collected during traverses across megaripples for the first 710 sols (Mars days) of the mission, laboratory‐based single‐wheel soil experiments, full‐scale rover tests at the Dumont Dunes, Mojave Desert, California, and numerical simulations show that a combination of material properties and megaripple geometries explain the high wheel sinkage and slip events. Extensive megaripple deposits have subsequently been avoided and instead traverses have been implemented across terrains covered with regolith or thin windblown sand covers and megaripples separated by bedrock exposures.